2017
DOI: 10.1016/j.micromeso.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preparation procedure on catalytic activity of PdBEA zeolites in aqueous phase hydrodechlorination of 1,1,2-trichloroethene

Abstract: Pd-loaded BEA zeolites containing 1 wt % of Pd were prepared by a two-step postsynthesis method (PdSiBEA and PdSiAlBEA) and a conventional wet impregnation (PdHAlBEA). Modification of BEA zeolite resulted in the introduction of Pd ions into zeolite framework as pseudo-tetrahedral Pd(II) and extra-framework octahedral Pd(II) evidenced by XRD, DR UVvis and TPR measurements. Calcination of as prepared zeolites in air at 773 K for 3 h and then reduction in 10 % H 2 /Ar flow at 873 K for 3 h led to obtain red-C-PdS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…It is an elimination-based remediation technique in which chlorinated compounds react with H 2 and are catalytically converted to chloride-free hydrocarbons and HCl. There has been ongoing research on HDC of chlorinated compounds where promising conversions and catalytic activities were obtained with the palladium-based state-of-the-art catalysts. The existing hydrodechlorination catalysts reported in the literature, however, suffer from catalyst poisoning due to anionic species present in real groundwater, inhibition by the unavoidable reaction product HCl, the formation of carbonaceous species on active sites, and active metal leaching. ,, In our present contribution, studies were performed to confirm whether active metals can be selectively located in the swollen matrix of SOMS and to understand the behavior of the active sites with respect to different reactive environments. Catalytic activity experiments and characterization studies were performed to examine properties of SOMS and Pd-incorporated SOMS in their unswollen and swollen states.…”
Section: Introductionmentioning
confidence: 84%
“…It is an elimination-based remediation technique in which chlorinated compounds react with H 2 and are catalytically converted to chloride-free hydrocarbons and HCl. There has been ongoing research on HDC of chlorinated compounds where promising conversions and catalytic activities were obtained with the palladium-based state-of-the-art catalysts. The existing hydrodechlorination catalysts reported in the literature, however, suffer from catalyst poisoning due to anionic species present in real groundwater, inhibition by the unavoidable reaction product HCl, the formation of carbonaceous species on active sites, and active metal leaching. ,, In our present contribution, studies were performed to confirm whether active metals can be selectively located in the swollen matrix of SOMS and to understand the behavior of the active sites with respect to different reactive environments. Catalytic activity experiments and characterization studies were performed to examine properties of SOMS and Pd-incorporated SOMS in their unswollen and swollen states.…”
Section: Introductionmentioning
confidence: 84%
“…As the NPs are isolated from others NPs due to their encapsulation on the zeolite cages and different channels, the catalytic activity can be improved, as well as the stability [20]. Due to this, zeolites are commonly used in liquid phase hydrodechlorination reactions [13,21,22], however, fewer studies have been applied to gas phase HDC [23][24][25][26]. In those gas-phase studies, conversion usually decreased after a few hours on stream, high selectivities to methane were obtained, and/or very low reactant inlet concentrations (below 100 ppm) were used [23,27,28].…”
mentioning
confidence: 99%
“…Oyama found that the catalytic performance of MoP/Al 2 O 3 was superior to that of Ni‐Mo‐S/Al 2 O 3 for hydrotreating. Therefore, the potential of transition metal phosphides (TMPs) as catalysts for hydrodesulfurization (HDS),, hydrodenitrification (HDN),, Hydrodeoxygenation (HDO), and hydrodechlorination (HDC) has been explored. Most researchers agree that phosphorus atoms are doped into the transition metal lattice in TMPs.…”
Section: Introductionmentioning
confidence: 99%